2015
DOI: 10.1177/0004867415615947
|View full text |Cite
|
Sign up to set email alerts
|

The oral health of people with chronic schizophrenia: A neglected public health burden

Abstract: Dental disease in people with schizophrenia deserves the same attention as other comorbid physical illness. The disparity in oral health is most marked for dental decay. Possible interventions include oral health assessments using standard checklists designed for non-dental personnel, help with oral hygiene, management of iatrogenic dry mouth and early dental referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 38 publications
5
62
1
8
Order By: Relevance
“…The authors concluded that dental disease deserves the same attention as other comorbidities for people with schizophrenia (Wey et al . ). These findings suggest that oral health needs to be part of optimising physical health care for patients with chronic mental illness.…”
Section: Discussionmentioning
confidence: 97%
“…The authors concluded that dental disease deserves the same attention as other comorbidities for people with schizophrenia (Wey et al . ). These findings suggest that oral health needs to be part of optimising physical health care for patients with chronic mental illness.…”
Section: Discussionmentioning
confidence: 97%
“…Schizophrenia is a chronic and disabling mental disorder affecting 1–2% of the population worldwide, characterized by heterogeneous clinical features (Lu et al., 2012; Wey, Loh, Doss, Abu Bakar, & Kisely, 2016). Although the underlying etiology of schizophrenia is still poorly understood, lines of evidence suggest that dysfunction in 5‐hydroxytryptamine (serotonin) processes involves in the pathophysiology of schizophrenia (Ellenbroek & Prinssen, 2015; Wooley & Shaw, 1954).…”
Section: Introductionmentioning
confidence: 99%
“…Some treatments can cause gingival pain (ziprazidone) (44) and problems with the temporomand ibular joint (trismus) (45). Generally, schizophrenic patients with atypical antipsychotics have better dental health than patients treated with typical antipsychotics or a combination of both (37).…”
Section: The Factors That Influence the Dental Treatment Of Patients mentioning
confidence: 99%
“…In response to the increase in chronic diseases, the very high rate of treatment non-observance and the need for more patient autonomy, the partner patient concept is gradually emerging as a healthcare approach (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). The experiential knowledge of patients in psychiatry was used to establish the charter of citizenship, which opens up prospects in terms of healthcare system reorganization (55,56).…”
Section: The Partner Patient Conceptmentioning
confidence: 99%